Análise quantílica-espacial de determinantes de preços de imóveis urbanos com matriz de bairros: Evidências do mercado de Belo Horizonte - Bernardo Alves Furtado (Instituto de Pesquisa Econômica Aplicada (IPEA), 2011)
– This paper analysis two central influences on real estate urban market: i) neighborhood as cognitively-perceived identity units; and ii) heterogeneity of preferences of households. In doing so, two methodological changes are applied. Firstly, a neighborhood spatial matrix is proposed and compared to regularly used matrices and, secondly, a spatialquantile regression is tested. The results highlight the fact that spatial influence brought to regression models through weight matrix should be carefully used, and that the matrix's choice might carry unobserved and unwanted effects into the estimation. Results also demonstrated that using information of neighborhood identity can optimize the understanding of city's complex influence on real estate markets. Finally, the quantile estimation should always be tested against in real estate estimation, as preferences of households seem to differ significantly for different levels of prices.
Keywords: R20; C21; 330; Städtischer Immobilienmarkt; Belo Horizonte